Improvement Capacity Mitigation Disaster Floods in the Village Tambakrejo Through Early Warning System - Naryatmojo, Deby Luriawati; Kusumantoro, Kusumantoro; Khatamy, Muhammad Adam (Universitas Negeri Semarang, 2025)
This community service activity aims to enhance community capacity for flood disaster mitigation in Tambakrejo Village, Semarang City, through strengthening the management of the Early Warning System (EWS). Tambakrejo is a coastal area vulnerable to floods and tidal inundation due to land subsidence and sea level rise. The main problems include low community preparedness and suboptimal management of the existing EWS. The implementation method involved training, mentoring, and the development of Standard Operating Procedures (SOP) for the local Disaster Preparedness Group (KSB) as the main partner, carried out through stages of socialization, capacity building, implementation, and evaluation. The results showed improved knowledge and skills of KSB members in operating and maintaining the EWS device, along with the creation of a management SOP serving as an operational guide at the community level. This activity demonstrates that community capacity building through participatory and technology-based approaches can strengthen disaster mitigation systems and enhance community preparedness against flood risks in coastal areas.